stylistics of Sa'di's quatrain - Omid Majd; Nasrin Sayyedzade (مطالعات زبانی و بلاغی)
This paper intends to investigate the rhetorical and stylish features of the Sa’di quatrain. This poetic format/form doesn’t enjoy the significant frequency compared to the entire relics of the poet; however, its study and cognition is of the significance because he has expressed a part of his feelings, desires and ideals in this poetic format. In order to achieve this goal, the quatrains of this poet have been studied at three lingual, literal and intellectual levels and endeavor has been made to determine his exclusive and style making elements and the axial thought as well as the spirit dominant on his quatrains texture should be revealed. The interesting point is that the major part of his quatrains sounds to be short lyrics that express the very thoughts dominant on his lyrics in a smaller container/form and the other part of it encompasses his thoughts of advice in Boostan and Golestan. His language in these poems is of the same sonnet poetry; that is   Easy and Unobtrusive. He has not been powerful in composing this poetic template/style, unlike his other works.